Isolation and Characterization of Escherichia coli tolC Mutants Defective in Secreting Enzymatically Active Alpha-Hemolysin - Vakharia, Hema (American Society for Microbiology, 2001)
This study describes the isolation and characterization of a unique class of TolC mutants that, under steady-state growth conditions, secreted normal levels of largely inactive alpha-hemolysin. Unlike the reduced activity in the culture supernatants, the cell-associated hemolytic activity in these mutants was identical to that in the parental strain, thus reflecting a normal intracellular toxin activation event. Treatment of the secreted toxin with guanidine hydrochloride significantly restored cytolytic activity, suggesting that the diminished activity may have been due to the aggregation or misfolding of the toxin molecules. Consistent with this notion, sedimentation and filtration analyses showed that alpha-hemolysin secreted from the mutant strain has a mass greater than that secreted from the parental strain. Experiments designed to monitor the time course of alpha-hemolysin release showed delayed appearance of toxin in the culture supernatant of the mutant strain, thus indicating a possible defect in alpha-hemolysin translocation or release. Eight different TolC substitutions displaying this toxin secretion defect were scattered throughout the protein, of which six localized in the periplasmically exposed α-helical domain, while the remaining two mapped within the outer membrane-embedded β-barrel domain of TolC. A plausible model for the secretion of inactive alpha-hemolysin in these TolC mutants is discussed in the context of the recently determined three-dimensional structure of TolC.